Faktor Perilaku Pencegahan Penularan Virus COVID-19 di Desa Labuan - Milla Evelianti Saputri; Susanti Widiastuti; Rizka Olivia (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Indonesia is one of the countries affected by the spread of COVID-19. This study aims to look at the factors associated with preventing the transmission of COVID-19, with a cross-sectional design. Research subjects were selected by simple random sampling technique. Data were collected through filling out a questionnaire and then analyzed using the Chi-Square test. The results of the analysis showed that the p-values for each factor were: age = 0.002, gender = 0.004, knowledge = 0.000 and attitude = 0.000. Furthermore, it was concluded that age, gender, knowledge and attitudes were factors in the behavior of the spread of COVID-19.Keywords: COVID-19; age; gender; knowledge; attitude; preventive behavior ABSTRAK Indonesia merupakan salah satu negara yang terkena penyebaran COVID-19. Penelitian ini bertujuan untuk melihat faktor-faktor yang berhubungan dengan pencegahan penularan COVID-19, dengan rancangan cross- sectional. Subyek penelitian dipilih dengan teknik simple random sampling. Data dikumpulkan melalui pengisian kuesioner lalu dianalisis menggunakan uji Chi-Square. Hasil analisis menunjukkan nilai p untuk masing-masig faktor adalah: usia = 0,002, jenis kelamin = 0,004, pengetahuan = 0,000 dan sikap = 0,000. Selanjutnya disimpulkan bahwa usia, jenis kelamin, pengetahuan dan sikap merupakan faktor dari perilaku penyebaran COVID-19.Kata kunci: COVID-19; usia; jenis kelamin; pengetahuan; sikap; perilaku pencegahan